Chapter 5 An Idea Incarnated in an Individual German Philosophy and the First Marshal of Poland : Triumphal March, 1931 - Budziak, Anna (Taylor & Francis, 2022)
Written when Eliot rekindled his interest in Husserl and turned his attention to Heidegger, Triumphal March can be interpreted as a poem performing a philosophical experiment: it depicts the figure of a leader as seen in the light of Husserl's Ideas and within the perspective of Heidegger's Being and Time. This chapter, stressing philosophical contexts and sustaining its focus on the incarnational metaphor, argues that Eliot-while glamorizing a king who "incarnates the idea of the Nation"- in practice, turned his attention to the leader incarnating a philosophy: the persona of Marshal Piłsudski emerging from The Memories of a Polish Revolutionary and Soldier, which Eliot read in his capacity as a director of Faber and Faber, and in the context of German philosophy.